Macronutrient composition of a morning meal and the maintenance of attention throughout the morning. (26th November 2018) - Wilson, Tommy J.; Gray, Michael J.; Van Klinken, Jan-Willem; Kaczmarczyk, Melissa; Foxe, John J.
Abstract : Background: At present, the impact of macronutrient composition and nutrient intake on sustained attention in adults is unclear, although some prior work suggests that nutritive interventions that engender slow, steady glucose availability support sustained attention after consumption. A separate line of evidence suggests that nutrient consumption may alter electroencephalographic markers of neurophysiological activity, including neural oscillations in the alpha-band (8–14 Hz), which are known to be richly interconnected with the allocation of attention. It is here investigated whether morning ingestion of foodstuffs with differing macronutrient compositions might differentially impact the allocation of sustained attention throughout the day as indexed by both behavior and the deployment of attention-related alpha-band activity. Methods: Twenty-four adult participants were recruited into a three-day study with a cross-over design that employed a previously validated sustained attention task (the Spatial CTET). On each experimental day, subjects consumed one of three breakfasts with differing carbohydrate availabilities (oatmeal, cornflakes, and water) and completed blocks of the Spatial CTET throughout the morning while behavioral performance, subjective metrics of hunger/fullness, and electroencephalographic (EEG) measurements of alpha oscillatory activity were recorded. Results: Although behavior and electrophysiological metrics changed over the course of the day, no differences in their trajectories were observed as a function of breakfast condition. However, subjective metrics of hunger/fullness revealed that caloric interventions (oatmeal and cornflakes) reduced hunger across the experimental day with respect to the non-caloric, volume-matched control (water). Yet, no differences in hunger/fullness were observed between the oatmeal and cornflakes interventions. Conclusion: Observation of a relationship between macronutrient intervention and sustained attention (if one exists) will require further standardization of empirical investigations to aid in the synthesis and replicability of results. In addition, continued implementation of neurophysiological markers in this domain is encouraged, as they often produce nuanced insight into cognition even in the absence of overt behavioral changes. ClinicalTrials.gov Identifier: NCT03169283